AKTIVITAS HARIAN NAMDUR POLOS PERIODE SEBELUM KAWIN PADA KAWASAN PEGUNUNGAN ARFAK DISTRIK SURUREY ANGGI BARAT - Jan Hendriek Nunaki (FMIPA Universitas Papua, 2002)
A research has been done on the daily activities of “Namdur Polos” or Bowerbird (Amblyornis inornatus) on the pre-copulation period in the Arfak Montain Protected Areas, especially in the district of Sururey, West Anggi. The variables observed in the research are decoration, feeding, socialization and home range activities. The result shows that Namdur Polos spend 8,5% in decoration, 10,2% in feeding and 81,3% in socialization. It was concluded that the bowerbird invests a lot of time on the social activity during the pre copulation period, shown by playing on the twigs above the “copulation hut”.